A new predictive tool for the early risk assessment of gestational diabetes mellitus. Issue 5 (October 2016) - Capula, Carmelo; Chiefari, Eusebio; Borelli, Massimo; Oliverio, Rosa; Vero, Anna; Foti, Daniela; Puccio, Luigi; Vero, Raffaella; Brunetti, Antonio
Highlights: A new predictive tool for the risk assessment of GDM. A new predictive tool in the management of GDM screening. A new predictive tool that reduces both screening tests and undetected GDM cases. A new predictive tool that improves the prevalence estimates of GDM. A new predictive tool that reduces the impact of GDM on healthcare costs. Abstract: Aims: The Italian National Institute of Health has recently introduced a selective screening based on the risk profile of pregnant women, which while recommending against screening of women at low risk (LR) for GDM, it recommends an early test for women at high risk (HR) for GDM. Herein, we assessed the accuracy and cost-effectiveness of this screening and developed a new index that improves these requirements. Methods: We retrospectively enrolled 3974 pregnant women. GDM was diagnosed with a 2 h 75-g OGTT at 16–18 weeks (early test) or 24–28 weeks of gestation, according to the IADPSG guidelines. Results: 55.6% of HR women had GDM, although only 38.4% underwent early screening. Among 2654 women at medium risk, 20.9% had GDM; paradoxically, among 770 LR women, that would not have been screened, 26.6% received a GDM diagnosis. Based on these unsatisfactory results, we elaborated the Capula's index, that reduced both screening tests ( p  < 0.001) and potentially undetected GDM cases ( p  < 0.001), and corrected the paradoxical prevalence estimates of GDM obtained with the current Italian guidelines. Also, Capula's index improved correlation of GDM risk profile with obstetric and neonatal adverse events. Conclusions: Capula's index improves accuracy of selective screening for GDM.